低層大氣擾動效應對低緯度電離層電漿擾動之影響 - 林建宏; 蕭棟元; 張起維 (2015)
計畫編號:MOST103-2111-M006-003-MY3 執行機構:國立成功大學地球科學系（所） 研究期間:2015-08~2016-07 本計畫旨在研究低層大氣擾動對赤道與低緯度電離層電漿不規則體(電漿泡)發展之影響。近年研究顯示，低層大氣於對流層對流旺盛區域產生大氣潮汐，可向上傳播至電離層?熱氣層高度，並影響低緯度電離層電漿分佈。此外，產生平流層瞬間暖化(Stratospheric Sudden Warming, SSW)之行星波會擾動全球大氣潮汐，造成熱氣球層風場與電離層電子密度擾動。本計畫將利用全天輝光影像儀、地面GPS接受機、旗標信號接收機觀測，以及NACRTIMEGCM與SAMI-3模式，研究對流層與平流層天氣系統動對赤道低緯度電離層電漿泡發展之影響。 This project plans to investigate the effect of lower atmospheric disturbances to low-latitude ionospheric irregularities (or plasma bubbles). Recent studies indicate that the latent heat released from tropospheric convection zone could produce upward propagating atmospheric tides. These tides, mainly the nonmigrating (non-sun-synchronized) components, could modify the thermospheric winds and lead to modification of ionospheric electric field and thus the electron densities. In addition to effect from tropospheric origins, the planetary wave responsible to stratospheric sudden warming (SSW) could alter the global thermospheric tides and winds and lead to ionospheric modifications. As the growth rate of equatorial ionospheric plasma instability depends on ionospheric electric field, conductivity, lower boundary density perturbations, and thermospheric winds, the development of plasma bubbles is relevant to thermospheric and ionospheric modifications from troposphere and stratosphere. With an all sky imager of airglow, ground-based GPS receiver network, beacon receiver network, we plan to observe the interconnection between the lower atmosphere condition and bubble development. The observations results will be further modeled using NCAR Thermosphere Ionosphere Mesosphere Electrodynamic General Circulation Model (TIMEGCM) together with NRL SAMI3 model.